Native Bacillus paralicheniformis isolate as a potential agent for phytopathogenic nematodes control - Chavarria-Quicaño, Estefany; Contreras-Jácquez, Victor; Carrillo-Fasio, Armando; De la Torre-González, Francisco; Asaff-Torres, Ali (Frontiers in Microbiology, 2023)
Phytopathogenic nematodes (PPNs) are responsible for substantial damages within agricultural crops worldwide which can be controlled employing beneficial microorganisms and/or their metabolites in an ecofriendly way. Nevertheless, the success of the control regards not only on the virulence of the strains or the toxicity of their metabolites but also on their ability to colonize and remain in the rhizospheric environment, particularly in those crops affected by abiotic stresses promoted by the climate change. Consequently, the bioprospection of beneficial microorganisms able to control PPNs and to thrive in adverse conditions has attracted attention. On this way, deserts are perfect ecological niches to isolate microorganisms adapted to harsh conditions due to its extreme environment conditions. The purpose of this research was to isolate and characterize bacteria from rhizospheric soil samples collected in the Northwestern Desert of Mexico with potential for PPNs control. As first screening, secretomes of each isolate were tested in vitro for nematicidal activity (NA). Then, activities from secretomes and endospores from the selected isolate was confirmed in vivo assays. From 100 thermotolerant isolates, the secretome of the isolate identified as Bacillus paralicheniformis TB197 showed the highest NA (˃95%) against Meloidogyne incognita, under in vitro and in vivo tests, also suppressing infections caused by M. enterolobii in tomato crops too. The endospores of TB197 strain showed a reduction of 81% in the severity infection caused by M. enterolobii (p≤0.05), while in open field tests the galling index (GI) was reduced 84% (p≤0.05) in tomato greenhouse-tests. Also, a reduction of the root necrosis (81%) caused by Radopholus similis in banana plantations, (p≤0.05) compared to the control was reported. Owing to their efficacy in controlling PPNs infections the endospores and secondary metabolites from B. paralicheniformis TB197 strain can be used in bionematicidal formulations.